Psychological and Socio-Economical Determinants of Health: The Case of Inner German Migration - Schmalbach, Bjarne; Schmalbach, Ileana; Kasinger, Christoph; Petrowski, Katja; Brähler, Elmar; Zenger, Markus; Stöbel-Richter, Yve; Richter, Ernst Peter; Berth, Hendrik (Frontiers in Public Health, 2021)
A substantial body of research has shown worse health conditions for East- versus West-Germany in the wake of Reunification. In the present study, we investigate how these differences between the two formerly divided regions came to be and what maintains them. Specifically, we consider the associations between health status, income satisfaction, and health-related locus of control. In a quasi-experimental design, we are particularly interested in the differences between individuals who stayed in East-Germany and those who were born in the East but migrated to West-Germany. To this end, we examined data from seven waves of the Saxony Longitudinal Study (2003-2009) which is comprised of adolescents at the time of Reunification. Specifically, we tested a cross-lagged panel model with random effects, which evinced very good model fit. Most parameters and processes were equivalent between individuals who stayed in East-Germany versus moved to West-Germany. Crucially, there was the expected pattern of positive correlations between health, income, and locus of control. In addition, we found substantially lower values for all three of these variables for the individuals who stayed in East-Germany (vs. moved to West-Germany). A likely cause is the increase in socio-economic status that the internal migrants experienced.